Female athletes and health - Malara, M.; Lutoslawska, G. (Biomedical Human Kinetics, 2016)
It is well documented that regular physical activity has a beneficial effect on human health by affecting the metabolic processes that are of fundamental importance in the body`s functions, such as insulin sensitivity and glucose disposal, as well as lipid and lipoprotein turnover. On the other hand, there is a wealth of studies which indicate that strenuous, regular physical activity, such as that performed by high performance athletes, may be detrimental for the athletes` health especially in women. This review focuses on the factors that contribute to health problems in female athletes, named the female athlete triad, which includes excessive dieting, menstrual dysfunctions (anovulatory menstrual cycles, oligomenorrhea, amenorrhea) and a low bone mineral density (BMD). As a result of these factors, women who participate in sports, especially those focused on leanness, need special attention and education from health professionals, coaches and the athletes themselves to prevent the detrimental effects of an inadequate energy supply against high energy demands.